Acellular Human Dermal Allograft Tuberoplasty Improved the Biomechanics in Mid-Range and Higher Abduction Angles in a Cadaveric Model of Massive Irreparable Rotator Cuff Tears - Ryan Lew, B.S; Maxwell Park, M.D; Ryan Beyer, B.S; Michelle H. McGarry, M.S; Manik Dham, M.S; Oliver Hauck, M.S; Gregory Adamson, M.D; Thay Q. Lee, Ph.D (Elsevier, 2024)
Purpose: To evaluate the biomechanical effects of acellular human dermal allograft tuberoplasty (AHDAT) in a cadaveric model of an irreparable supraspinatus + anterior one-half infraspinatus (stage III) rotator cuff tear. Methods: Eight cadaveric shoulders were tested at 20°, 40°, and 60° of glenohumeral abduction (AB) and 0°, 30°, 60°, and 90° of external rotation (ER). Superior humeral translation, acromiohumeral distance, and subacromial contact were quantified for 4 conditions: (1) intact, (2) stage III tear (entire supraspinatus and anterior one-half infraspinatus), (3) single-layer AHDAT, and (4) double-layer AHDAT. Results: Stage III tear significantly increased superior translation at 20° and 40° AB and all ER angles and at 60° AB/60° ER (P ≤ .045 vs intact). Compared to the stage III tear, the single-layer AHDAT significantly decreased superior translation at 60° AB/60° ER (P = .003), whereas the double-layer AHDAT significantly decreased superior translation at 40° and 60° AB at all ER angles except 60° AB/0° ER (P ≤ .028). The stage III tear significantly decreased acromiohumeral distance at 20° AB (P ≤ .003); both grafts increased acromiohumeral distance to intact levels (P ≥ .055 vs intact). Stage III tear increased subacromial contact pressure at 20° and 40° AB/0° and 30° ER and at 60° AB/30° and 60° ER (P ≤ .034). Both AHDAT groups decreased contact pressure at 40° AB/30° and 60° ER back to intact, whereas the double-layer AHDAT also decreased contact pressure at 20° AB/0° and 60° ER and 60° AB/30° ER (P ≥ .051 vs intact). Conclusions: Both single- and double-layer grafts for AHDAT improved superior translation, subacromial contact characteristics, and acromiohumeral distance after a stage III rotator cuff tear, with varying effectiveness due to the position-dependent nature of greater tuberosity to acromial contact with abduction. Clinical Relevance: The best treatment for massive or irreparable rotator cuff tears is a matter of concern. The results of this study will help determine whether an acellular human dermal allograft tuberoplasty is a potential treatment option worthy of further investigation.